The Impact of Job Satisfaction and Motivation on Work Performance of Lecturers at TEDC Polytechnic Bandung (The Indonesian Journal of Business Administration, 2021)
This study entitled The Impact of Job Satisfaction and Motivation on Work Performance of Lecturer at TEDC Polytechnic Bandung. The purpose of the research conducted by the author is to get the results of a study on job satisfaction, get the results of a study on motivation, and get the results of a study on the performance of the lecturers of TEDC Polytechnic Bandung. This study used a descriptive method using the Slovin formula to get the sample. Data processing was performed by multiple regression analysis and hypothesis testing. Based on the research results, it can be concluded that there is a significant effect of job satisfaction on performance. There is a significant effect of motivation on performance. There is a significant effect simultaneously of job satisfaction and motivation on TEDC Bandung Polytechnic lecturers' performance.Keywords: Job Satisfaction, Motivation, Performance